New Sodium Intercalation Cathode Prepared by Sodiation of Delithiated Host LiNi1/3Mn1/3Co1/3O2 - Van Hoang Nguyen; Le Minh Nguyen; Tuyen Thi Kim Huynh; Van Man Tran; My Loan Phung Le (Advances in Materials Science and Engineering)
In this work, the layered structure LiNi1/3Mn1/3Co1/3O2 (LiNMC) served as a host to enable sodium-ion intercalation. LiNMC was initially charged in Li-half-cell at C/25 rate up to 4.5 V to extract maximum of Li+ ions and then discharged at the same rate in Na-half-cell down to 2 V for full sodiation to form NayNMC phase. The electrochemical characteristics of the new sodium phase NayNMC were evaluated by cyclic voltammetry (CV), galvanostatic cycling, and electrochemical impedance spectroscopy (EIS). On the CV curve, the featured peaks of phase transition induced by Na+ intercalation into NayNMC host could be distinguished from the couple peak located at 3.8 V upon the Li+ intercalation into LixNMC. The high uniformity and crystallinity of the NayNMC phase enable delivering a good initial capacity of about 120 mAh g−1 with high rate capability up to 5 C rate. Energy-dispersive X-ray spectroscopy (EDS) confirms the presence of sodium element in the sodiated NayNMC. It was also noticed that the pristine O3-type layered structure remained unchanged after ion exchanging but the lattice parameters increased due to the large size of sodium-ions inserted into the structure.